G219(P) Social deprivation and upper respiratory tract infection in the north east. (25th October 2020) - Renouf, C; Battersby, A; Lim, E; Emonts, M; Parker, M; Moll, H
Abstract : Aims: This project aimed to identify a relationship between social deprivation and patients presenting to Paediatric A&E with upper respiratory tract infection (URTI) in [region]. It also aimed to analyse the geographic spread of URTI patients presenting to Paediatric A&E in the North East. Methods: This was a retrospective study using data from the European MOFICHE and PERFORM study databases. The postcodes of patients presenting to Great North Children's Hospital Paediatric A&E with a working diagnosis of URTI (n=1685) between April 2017 and March 2018 allowed classification of patients into Index of Multiple Deprivation (IMD) deciles using the English indices of deprivation 2015 tool. Individual patient postcodes were colour-coded by deprivation decile and pinned onto a visual map using the My Maps tool on Google Maps. Results: 58.4% of URTI patients in Paediatric A&E came from the most deprived households (IMD deciles 1 – 3), 15.7% from the least deprived households (IMD deciles 8 – 10) and 25.9% from households in between (IMD deciles 4 – 7). Whilst there was a general trend of decreasing patient presentation with decreasing levels of deprivation, there was a slight increase in patients in IMD deciles 9 and 10 (see table 1 ). This trend remained the same for both viral and bacterial URTIs. Patients from less deprived households were less likely to be discharged and more likely to be admitted, for both short (< 24 hours) and longer admissions (> 24 hours). Mapping of patient postcodes highlighted 'hotspots' of patients in the North East. Conclusion: There is a significant relationship between social deprivation and presentation to Paediatric A&E with URTI in the North East. Most patients presenting to Great North Children's Hospital Paediatric A&E with URTI came from more socially deprived backgrounds.